2010
DOI: 10.1016/j.phrs.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of quercetin-loaded microemulsion in the airways allergic inflammatory model in mice

Abstract: Quercetin is a plant-derived flavonoid widely known by its anti-oxidant and anti-inflammatory properties, but its oral bioavailability is very poor and this becomes difficult to assess its therapeutic potential. Here we have compared the anti-inflammatory effect of quercetin-loaded microemulsion (QU-ME) and quercetin suspension (QU-SP) in an experimental model of airways allergic inflammation. Mice received daily oral doses of QU-ME (3 or 10mg/kg; in an oil-in-water microemulsion content 0.02:0.2:1 of lecithin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(88 citation statements)
references
References 46 publications
2
83
0
3
Order By: Relevance
“…Recently, quercetin has been detected as an inhibitor of interleukin 1 beta (IL-1β) induced intercellular adhesion molecule-1 (ICAM-1) expression and nuclearfactor-kappa B (NF-κB) activity in human A549 lung cells [15]. Indeed oral administration of quercetin in animal models was reported to inhibit experimentally induced pulmonary fibrosis, [16] airway inflammation [17] and emphysema [18]. Mi et al [19] showed that quercetin suppressed oxidative damage characterized by lipid peroxidation, decreased spermatogonial cell numbers, vacuolated cytoplasm and condensed nuclei in spermatogonial cells of embryonic chicken exposed to 3-methyl-4-nitrophenol.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quercetin has been detected as an inhibitor of interleukin 1 beta (IL-1β) induced intercellular adhesion molecule-1 (ICAM-1) expression and nuclearfactor-kappa B (NF-κB) activity in human A549 lung cells [15]. Indeed oral administration of quercetin in animal models was reported to inhibit experimentally induced pulmonary fibrosis, [16] airway inflammation [17] and emphysema [18]. Mi et al [19] showed that quercetin suppressed oxidative damage characterized by lipid peroxidation, decreased spermatogonial cell numbers, vacuolated cytoplasm and condensed nuclei in spermatogonial cells of embryonic chicken exposed to 3-methyl-4-nitrophenol.…”
Section: Introductionmentioning
confidence: 99%
“…In another recent report by Lisi et al (2011) quercetin was shown to reduce cell proliferation and hyaluronan production. Quercetin has been shown to exhibit antioxidant, anti-inflammatory, and antiadipogenic properties in other cell systems and animal models (Comalada et al 2005, Rotelli et al 2009, Vasquez-Garzon et al 2009, Ying et al 2009, Rogerio et al 2010. Here, we investigated the anti-adipogenic role of quercetin in OFs stimulated by oxidants, such as CSE and H 2 O 2 , as well as associations between the anti-adipogenic and antioxidant effects of quercetin, including its reduction of ROS production.…”
mentioning
confidence: 99%
“…The antioxidant, free radical-scavenging, and neuroprotective effects of quercetin is well known (15)(16)(17) . Besides these important benefits of quercetin, it also has a protective effect against apoptotic cell damage.…”
Section: Discussionmentioning
confidence: 99%